Coffin man - Doss, James D. (New York : Minotaur Books, 2011)
"When Colorado rancher and part-time tribal investigator Charlie Moon gets a call from Wanda Naranjo, she's panicked. Not only is her sink leaking, which Moon graciously fixes, but her sixteen-year-old daughter, Betty, has gone missing. For how long? Only a few hours, but she's pregnant. So what about the father-to-be? It's a good question and anybody's guess. Betty has kept her lips sealed on the subject. And that's not all. Betty claimed to be going to see a school counselor on what turned out to be his day off. So was she running away or was she abducted? Moon's best friend, Granite Creek Chief of Police Scott Parris, doesn't believe any of it and suspects that Wanda tricked them into doing a little emergency plumbing. While it's enough to make Parris's blood boil, Moon can't shake the feeling that some other foul play might be at work."--Jacket.
edited hb 2015-06-16
Keywords: Missing persons -- Fiction; Moon, Charlie (Fictitious character : Doss) -- Fiction; Colorado -- Fiction; Mystery fiction